Pelatihan Penyusunan Proposal Guna Meningkatkan Pemahaman Metode Penelitian Bagi Mahasiswa - Mega Adyna Movitaria; Melda Delvia; Arif Ridha (Universitas PGRI Palembang, 2023)
The purpose of this service is to find out the understanding of STIT Ahlussunnah Bukittinggi students regarding research methodology in preparing research proposals. If students understand research methodology, it is hoped that they can be motivated to write various research forms with multiple methods. The main problem in this service is the lack of student understanding of research methodology, so to overcome this is to provide training related to research methodology. So that it can increase student understanding in further research. The methods of this service are presentation, question and answer, and demonstration. The desired result of this community service activity is an understanding of research methodology for STIT Ahlussunnah Bukittinggi students.Â The output target of this program is an increased understanding of research methodology for STIT Ahlussunnah Bukittinggi students. The data source studied was STIT Ahlussunnah Bukittinggi students